Nucleus accumbens deep brain stimulation in adult patients suffering from severe and enduring anorexia nervosa (STIMARS): protocol for a pilot study - Duriez, Philibert; Simboli, Giorgia Antonia; Domenech, Philippe; Buot, Anne; Halpern, Casey; Fadigas, Marie; Mongin, Yann; Guy-Rubin, Aurore; Carron, Romain; Oppenheim, Catherine; Gorwood, Philip; Pallud, Johan; et al. (Frontiers in Psychiatry, 2025)
BackgroundAffecting adolescent and young adults, anorexia nervosa (AN) has the highest death rate of all mental disorders. Effective treatment options are lacking and a significant proportion of patients develop severe and chronic forms of the disease with long-lasting functional impairment. Neurobiology of AN implicates the nucleus accumbens as a core structure of the ventral striatum highly connected to the prefrontal cortex, the insula and the limbic system. Several studies reported promising results of deep brain stimulation for treatment-resistant AN. The aim of this study was to investigate the safety and efficacy of bilateral nucleus accumbens deep brain stimulation in severe and enduring AN.Methods and analysisThis is a prospective, multicentre, single-arm, open-label, non-randomized pilot trial of bilateral nucleus accumbens deep brain stimulation for severe and enduring AN. Patients will be followed up for 24 months after deep brain stimulation. The main objective of this study is to measure the safety and feasibility of nucleus accumbens deep brain stimulation in this population. The recruitment rate will be collected prospectively. Potential deep brain stimulation efficacy will be monitored by changes in: 1) health-related quality of life; 2) weight; 3) eating disorder symptomatology; 4) neuropsychological changes of cognitive flexibility, habits formation, emotional processing and central coherence; 5) psychiatric comorbidities (anxiety, depression, obsession). Local field potential recordings during an exposure task will be proposed to the patients. Additionally, caregiver quality of life will be assessed.DiscussionWe present the design and rationale for a pilot study investigating the safety of nucleus accumbens deep brain stimulation for treatment resistant anorexia nervosa. This trial will provide an estimated effect size of nucleus accumbens deep brain stimulation for treatment-resistant anorexia nervosa to support future larger-scale clinical trials.